Achieving SDG 9 through Enhanced Local Revenue and Government Accountability in Indonesia - Ramadhani, Shela; Paranoan, Selmita; Furqan, Andi Chairil; Usman, Ernawati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the influence of Regional Original Revenue (PAD) and accountability on the achievement of Sustainable Development Goals (SDGs) 9. This study uses panel data from local governments in Indonesia during the 2018–2021 period, with a total of 2,050 observations. Analysis is carried out on each component of PAD, namely regional tax revenue, regional levies, the results of segregated regional wealth management, and other legitimate PAD. Accountability is measured through an audit opinion issued by the Audit Board (BPK) as a proxy for the quality of public financial governance. The results show that PAD generally has a positive effect on the achievement of SDG 9, although the effect varies depending on the type of PAD source. Regional tax revenues, regional levies, and other legitimate PAD contribute positively to infrastructure development and the industrial sector, while the results of segregated regional wealth management show inconsistent influences. In addition, accountability has also been shown to have a significant positive effect on the achievement of SDG 9, which indicates that transparent and accountable regional financial management strengthens the effectiveness of development policies. These findings imply that improving the quality and quantity of PAD needs to be accompanied by strengthening accountability so that sustainable development goals can be achieved optimally.